The effect of Edmodo in science learning on students' learning outcomes and critical thinking - Sukma Nurmawarni; Supeno Supeno; Aris Singgih Budiarso (Jurnal Penelitian Ilmu Pendidikan, 2022)
This study examines the effect of using Edmodo in science learning on student learning outcomes and critical thinking in learning organizational life systems. The type of research used is a quasi-experimental design with a posttest-only control group design. Determination of the sample using the purposive sampling method. The research population includes all seventh-grade students of SMP Negeri 1 Glenmore Banyuwangi. The samples used were students of class VII A as the experimental class and class VII B as the control class. Methods of data collection using tests. The data analysis technique used an independent-sample t-test. The independent sample t-test on learning outcomes obtained a significance value of 0.047 less than 0.05, which means that there are differences in learning outcomes between the experimental class and the control class. The independent sample t-test of students' critical thinking skills obtained a significance of 0.013 less than 0.05, which means that there is a significant difference in critical thinking skills between the experimental class and the experimental class. Edmodo can be used as an alternative media for online learning during the pandemic and classroom learning. In its implementation, teachers must have good classroom management skills so that learning can take place and provide good learning outcomes.Pengaruh Edmodo dalam pembelajaran IPA terhadap hasil belajar dan berpikir kritis siswaPenelitian ini bertujuan untuk mengkaji pengaruh penggunaan Edmododalam pembelajaran IPA terhadap hasil belajar dan berpikir kritis siswa dalam pembelajaran IPA pada materi sistem organisasi kehidupan. Jenis penelitian digunakan adalah kuasi eksperimen dengan posttest only control group design. Penentuan sampel menggunakan metode purposive sampling. Populasi penelitian meliputi seluruh siswa kelas VII SMP Negeri 1 Glenmore Banyuwangi. Sampel yang digunakan adalah siswa kelas VII A sebagai kelas eksperimen dan siswa kelas VII B sebagai kelas kontrol. Metode pengumpulan data menggunakan tes. Teknik analisisa data menggunakan uji independent sample t-test. Hasil uji independent sample t-test pada hasil belajar diperoleh nilai signifikansi sebesar 0,047 lebih kecil dari 0,05 yang berarti terdapat perbedaan hasil belajar antara kelas eksperimen dengan kelas kontrol. Hasil uji independent sample t-test kemampuan berpikir kritis siswa diperoleh signifikansi  0,013 lebih kecil dari 0,05 yang berarti bahwa terdapat perbedaan signifikan kemampuan berpikir kritis antara kelas eksperimen dengan kelas eksperimen. Edmodo bisa dijadikan alternatif media dalam pembelajaran online selama masa pandemi maupun pembelajaran di kelas. Dalam implementasinya, guru harus memiliki kemampuan mengelola kelas yang baik agar pembelajaran dapat berlangsung dan memberikan hasil belajar luaran yang baik.